(untitled) (Damu Journal of Sport Sciences, 2025)
The research aims to prepare exercises in the Superset style to develop explosive ability, strength characterized by speed, and accuracy of scoring with the inside foot in football for players under (20) years old, as well as identifying the effect of exercises in the Superset style to develop explosive ability, strength distinguished by speed, and scoring accuracy with the inside of the foot for individuals. Search sample. To achieve the goal, the researcher used the experimental method withe a pre- and post-test ffor its suitability to the research problem. The research community consists of Baghdad clubs for players under 20 years of age for Iraqi youth clubs, numbering (16) clubs, with a total number of players of (430), which represents a percentage of ( 100% of the number of players, As for the research sample, it was represented by the Al-Sinaa Sports Club players for the youth category, who numbered (26) players, with a percentage of (6.05%). The research sample was chosen randomly through a lottery, and the goalkeepers (4) were excluded, as well as (4) players were excluded due to injury. Failure to adhere to the training modules, The researcher conducted a pre- and post-test for the members of the research sample, and the appropriate statistical treatments were carried out. The researcher concluded that the plyometric exercises in the Superset style led to raising the level of the muscular abilities of the research sample, and thus this was reflected in the development of the explosive ability and the strength distinguished by speed of the legs, and that the plyometric exercises in the Superset style had contributed. In raising the level of competition among sample members, which led to positive results. The researcher recommends the need for coaches to pay attention to using the Superset method in order to develop the physical qualities of players in other team or individual games and for different categories, as well as choosing plyometric exercises similar to skill performance in the game to benefit from them in developing special skills in the game, and the need for those concerned with the game to pay attention to holding training courses. About using the